The Influence of Price and Celebrity Endorsement via Instagram on Generation Y Tourists' Purchase Interest at The St. Regis Bali Resort - Dwilestari, Ni Kadek; Pitanatri, Putu Diah Sastri; Suastini, Ni Made (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
This research analyzes and recognizes the influence of price and celebrity endorsement via Instagram on the purchase intention of generation Y tourists at The St. Regis Bali Resort. The method of collecting information in this research is a questionnaire. The population used in this research is active followers of The St. Regis Bali Resort's Instagram social media with the criteria of being born in 1980-1995 and have not had the chance to stay at The St. Regis Bali Resort. The number of illustrations in this research is 100 respondents with illustration taking using the purposive sampling method. The questionnaire will be distributed using google form. The information analysis method used is the classical assumption test, multiple linear regression analysis, t-test, F-test, and coefficient of determination with the support of the SPSS for windows version 29 program. The results of this research show that there is a positive and significant influence partially or simultaneously between price and celebrity endorsement on the purchase intention of generation Y tourists at The St. Regis Bali Resort. Price and celebrity endorsement have an influence of 65.2% on the purchasing attention of generation Y tourists, while the remaining 34.8% is due to other variables not mentioned in this research, such as position and brand image.